Maxillary Implant Placement in a Limited Residual Bone Height - Kurnia, Calvin; Wibisono, Jane Amelia V.; Sumantri, Dominica Dian S. (UI Scholars Hub, 2021)
The limitation of residual bone height (RBH) and vital structures such as sinuses in the maxillary often make the implant placement procedure becomes complicated. Clinicians may perform sinus elevation prior to implant placement to accommodate the length of the implant fixture. Sinus elevation is an invasive procedure and complication may occur during the surgery including the most frequent complication is perforation of Schneiderian membrane. Objectives: To discuss a comprehensive management of implant placement and its complication step by step from surgical procedures to crown placement. Case Report: 67-year-old female patient with partial edentulism in the right maxillary region, presence of sinus septum, and RBH was 4mm. The patient was planned to do sinus elevation surgery prior to implant placement, perforation of the Schneiderian membrane occurred while surgery performed and pericardium membrane was attached around the perforation site. Sinus re-entry and implant placement were performed after 3 months followed by prosthetics procedures in the next 6 month. Conclusion: Dental implant is a complicated treatment and complication may occur during the placement, thus a comprehensive management is very essential to minimize the risk of complications.